The Future of public housing. Ongoing trends in the East and the West. - (:unkn) unknown (Springer, 2013)
Public housing was once an important strand in western housing policies, but is seldom seen as a mainstream policy instrument for the future. In contrast, in many East Asian countries large public housing programs are underway. Behind these generalizations, there are exceptions, too. By including perspectives of scholars from across the world, this book provides new insights into public housing in its various forms. It contains in-depth chapters on public housing in five East Asian countries and six Western countries, together with three comparative overview chapters.
Keywords: Wohnungsbau; Sozialer Wohnungsbau; Wohnungsbauprogramm; Wohnungspolitik; Wohnungsbauförderung; Öffentlicher Wohnungsbau; Öffentliches Wohnungsunternehmen; Internationaler Vergleich; Anspruchsvoraussetzung; Fallbeispiel